Evoluç\~ao da pobreza extrema e da desigualdade de renda na Bahia: 1995 a 2009 - Rafael Guerreiro Osorio; Pedro H. G. Ferreira de Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Herein a characterization of the evolution of extreme poverty and income inequality in Bahia is presented. Extreme poverty and income inequality in Bahia fell twice from 1995 to 2009, in roughly the same periods, but at different pace. The first fall begins in 1996. For extreme poverty, it was a sudden fall ending in 1997, whilst inequality kept falling till 1999. After 1997 e 1999, extreme poverty and income inequality were stagnant up to 2003, when the second fall starts. This time, the income inequality fall was abrupt and ended in 2004, while extreme poverty diminished until 2006. The second fall took both to a lower level where they remained in 2009. Inequality measured by the Gini coefficient was stable about 0,55, and the extreme poverty rate was around 10% of the state population.
Keywords: I32; 330; Armut; Einkommensverteilung; Bahia